The only road - Diaz, Alexandra (Simon & Schuster Books for Young Readers, 2016)
Everyone in Jaime's small town in Guatemala knows someone who has been killed by the Alphas, a powerful gang that's known for violence and drug trafficking. Miguel, Jaime's cousin and best friend, was killed and Jaime fears that he is next. With his cousin Ángela, Jaime must risk everything and flee his home to live with his older brother in New Mexico.